Use of Macrozoobenthos for Water Quality Monitoring in Ecotourism Area of Prafi River, Manokwari, West Papua - Sabarita Sinuraya; Endang Arisoesilaningsih; Suharjono Suharjono; Catur Retnaningdyah (Program Pascasarjana, 2018)
The aim of research is to monitor the water quality of some ecotourism sites along Prafi Rivers (Manokwari, West Papua), especially in Subsay, SP1 reservoir and SP3 reservoir using macro-zoobenthos biotic index, Prati’s index and some chemical-physical factors of water. Research was done from July to September 2016. Sampling was performed through Purposive Random Sampling. Macro-zoobenthos was collected from each sampling sites in three locations, (upstream, middle stream, downstream) using Surber net and hand net. Water quality was categorized based on Implicit Prati’s Pollution index that is derived from DO, BOD5, pH, nitrate, orthophosphate and water temperature value. Macro-zoobenthos data was used to analyze the diversity index and six biotic indices. Result of the study showed that DO, BOD5, pH and nitrate value in all location meet water standard quality based on PP. no 82, 2001 class II (fisheries, recreation, animals husbandry and irrigation). The turbidity value in sites of upstream, middle stream and downstream Subsay and SP3 have meets standard water quality according to WHO for drinking water (<5 NTU). Based on the Prati’s index, the water quality was ranging from excellent to acceptable categories with value 0.4-1.9. The taxa richness of macro-zoobenthos was 31 taxa. The shannon-wiener diversity index in all stations were more than 2, indicated that the water was not polluted. The water quality of all station showed very excellent up to moderates (based on FBI), very excellent up to very bad (HBI), and excellent up to less polluted (ASPT). Percentage of Ephemeroptera, Plecoptera, and Trichoptera (% EPT) in all station up to 50% (excellent), except in station SP3 upstream (40%). EPT richness value in all station excellent to moderate. It can be concluded that the water quality of Subsay in upstream, middle stream, downstream and downstream of SP3 was excellent.The middle stream of SP3 and middle stream of SPI has moderate quality, while the water quality in SP3 upstream, SPI upstream and SPI downstream was bad.Keyword: Ecotourism, water quality, Prafi River.